Bioassays for detecting residues of fungitoxic compounds through bioautography, bioelectrophoresis and thin-laver diffusion - Zambolim, Laércio; Junqueira, Nilton Tadeu V.; Chaves, Geraldo Martins; Romeiro, Reginaldo da Silva; Oliveira, João Sabino de (Pesquisa Agropecuaria Brasileira, 2014)
The bioautographic technique on thin-layer chromatograms was compared to bioelectrophoresis and thin-layer diffusion for detecting fungitoxic compound by using Thielaviopsis paradoxa as test fungus. The bioelectrophoresis and thin-layer diffusion methods were described and employed for the first time. The methods were illustrated by bioassaying the fungicides mancozeb, captafol, benomyl and triadimefon in different concentrations. The minimum concentration of fungitoxic compounds detected was the same for three techniques employed, but it did vary with the fungicides. The minimum concentrations detected of benomyl, captafol, triadimefon and mancozeb were 0.04, 0.06, 1.25 and 1.90 ppm, respectively. The bioelectrophoresis technique gave the highest inhibition zone of the test fungus by using higher concentrations of the fungicides. The thin-layer diffusion technique may be of great value, because it is a simple, rapid, sensitive as the bioautographic technique on the detection of fungitoxic compounds.